POTENSI KEBERADAAN SENYAWA AKRILAMIDA DALAM MAKANAN - Oktaf Rina; Abdi Dharma; Afrizal Afrizal (Program Studi Analisis Farmasi dan Makanan Universitas Malahayati, 2021)
This of the study was to examine the potential presence of acrylamide compounds in foods containing the amino acid asparagine and reducing sugars that are processed at high temperatures. The initial research was carried out to determine the levels of precursors in the raw material and then analyzed the amount of acrylamide using HPLC-RP LC-6A Shimadzu with a C18 column and sterile aqueous mobile phase. The optimization condition of the instrument was achieved with a column temperature of 35oC, a wavelength of 254 nm and a flow rate of 0.8 mL/min. The retention time of acrylamide was observed at 3.8 min. The food sample tested was banana chips. The results showed that banana chips with a moisture content of 7.74% (w/w) ± 0.01 contained acrylamide 115.5 to 565 g/kg. Acrylamide content is influenced by the amount of precursor, temperature and duration of food processing.